Nonlinear optical characteristics of Nile blue films doped with the polymers PMMA, PVC and their blend by using z-scan technique - Jaffar, Amal F. (Iraqi Journal of Science, 2025)
The nonlinear optical characteristics of the laser dye Nile blue doped with Polyvinyl chloride (Nb /PVC), poly methylmethacrylate Nb/ (PMMA) and their blend N /(blend of PMMA 50 %+PVC 50%) was studded. Free-casting technique method was used for deposited the films. The nonlinear properties of the films studded  by using Z- scan technique .Z-scan experiment was performed using continuous wave (CW) diode laser at 650 nm in two parts with power of 50 mw . The first part was done using a closed-aperture placed in front of the detector to measure the nonlinear refractive index ,with the second part; the aperture in front the detector was removed (open aperture) to measure the nonlinear absorption coefficient. The open-aperture curve exhibits a normalized transmittance (valley), indicating the presence of induced absorption. The observed nonlinearity is found to be of the third order, as it fits to two photon absorption process (TPA). The closed-aperture curve exhibits a peak to valley shape, indicating a negative value of the nonlinear refractive index n2. The effective values of the nonlinear refractive index n2, the nonlinear absorption coefficient β2, real and imaginary parts of the third-order optical nonlinearity, χ(3) for Nb/PMMA+PVC films comparatively with that of Nb/PMMA and Nb/PVC has much lower optical transmittance value obtained shows that these films can be used as efficient optical limiters.